1985
DOI: 10.1007/bf00695189
|View full text |Cite
|
Sign up to set email alerts
|

Study of the contractile effect of 5-hydroxytryptamine (5-HT) in the isolated longitudinal muscle strip from guinea-pig ileum

Abstract: The contractile effect of 5-HT in the isolated longitudinal ileal muscle of adult guinea-pigs was studied over a large concentration range. 5-HT produced a biphasic concentration-response curve indicative of an interaction with at least two independent populations of receptors. The concentrations which elicited half-maximal effects for the first and the second phases of the concentration-response curve were estimated as 1.5 +/- 1.2 X 10(-8) mol/l and 1.3 +/- 0.4 X 10(-6) mol/l respectively. The maximal respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
98
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(120 citation statements)
references
References 18 publications
20
98
2
Order By: Relevance
“…It is known that agonists of the 5-HT receptors increase the release of acethylcholine from the motor nerve ending within the intestinal muscle and facilitate peristalsis and may be involved in mechanismsat 5-HT 3 receptors (35)(36)(37). However, in the present study granisetron at a concentration as high as 1.0 ”M failed to significantly modify relaxation and contractile responses to EFS.…”
Section: Discussioncontrasting
confidence: 77%
“…It is known that agonists of the 5-HT receptors increase the release of acethylcholine from the motor nerve ending within the intestinal muscle and facilitate peristalsis and may be involved in mechanismsat 5-HT 3 receptors (35)(36)(37). However, in the present study granisetron at a concentration as high as 1.0 ”M failed to significantly modify relaxation and contractile responses to EFS.…”
Section: Discussioncontrasting
confidence: 77%
“…It was suggested that both neuronal and non-neuronal 5-HT receptors in the lon gitudinal muscle of guinea pig ileum were involved in the 5-HT-induced contraction (1)(2)(3)(4)(5)(6)(7)(8). Although the nature of the non-neuronal 5-HT receptor remains unclear, the neuronal 5-HT receptor was defined as the 5-HT3 and 5 HT4 receptor subtypes which mediated acetylcholine re lease (7).…”
Section: Resultsmentioning
confidence: 99%
“…In the gastrointestinal tract, 5-HT is reported to contribute to the regulation of the motility and secretion via several 5-HT-receptor subtypes. The in volvement of the 5-HT-receptor subtype in 5-HT-induced intestinal contraction has been well-examined in the guinea pig small and large intestines (1)(2)(3)(4)(5)(6)(7)(8). In contrast, the effect of 5-HT on the regulation of intestinal motility has not been established in species other than guinea pigs.…”
Section: -Hydroxytryptaminementioning
confidence: 99%
“…In this study, ICS-205-930 strongly inhibited EM523 as well as motilin-induced gas tric contractions. 5HT3 receptors are reported to be dis tributed in the area postrema (12)(13)(14), the enteric nervous system (15)(16)(17) and afferent vagus nerves (14,17,18) in ferrets, rats and guinea pigs. Boeckxstaens et al (19) reported that stimulation of the 5HT3 receptors resulted in acetylcholine-mediated contractions through choliner gic efferent nerves in the canine ileal myenteric plexus.…”
Section: Discussionmentioning
confidence: 99%